Casos de ensino e professoras iniciantes - Nono, Maévi Anabel (2005)
The comprehension of the formative processes lived by teachers and the definition of the professional knowledge that forms the base of their performance appear as central themes in studies on teacher education, especially since the 80 s. Teachers are seen, in these studies, as professionals that make decisions in face of school events, solve dilemmatic situations in their classrooms, harbor beliefs that influence their professional activity, and build professional knowledge complex, dynamic and multifaceted when facing and reflecting on diverse situations that occur in the classrooms they teach and the school institutions they belong to. There has been wide investigation on the ways these things happen, as well as the way the processes of professional development of teachers are promoted. Different formative and investigative strategies of such processes have been proposed and analyzed. In this context, teaching cases have been pointed out as tools of great formative and investigative value, whenever the processes of learning and professional development of teachers are concerned (HAMMERNESS; DARLINGHAMMOND; SHULMAN, L., 2002; MARCELO GARCIA; MAYOR RUIZ; SÁNCHEZ MORENO 2002; MERSETH, 1996; MIZUKAMI, 2000; SHULMAN, J., 2002). In this study, we discuss data of qualitative nature referring to a research-intervention, that had as its objective the investigation of the feasibility of the use of teaching cases as instruments capable to bring to surface the professional knowledge of beginning teachers of the early Childhood Education and Elementary School, as well as provide grounds for the promotion of said knowledge. The data sources were narratives written by the teachers in different contexts. Studies have evidenced the importance the first years of the teaching career in the formative processes (ABARCA, 1999; TARDIF; RAYMOND, 2000; TARDIF, 2002). It is a period of survival and discovery, in which teachers seek to adjust their expectations and ideals regarding their profession to the real conditions of work that they end up facing, dealing with a series of limitations that act directly on their performance, while trying to remain in the profession and balancing contradictory feelings. In this inquiry, during the years of 2003/2004, four beginning teachers analyzed teaching cases that contemplated school situations faced by other teachers, and constructed a teaching case from experiences lived during the initial years of their teaching career. It can be said that the strategies of analysis and writing of the teaching cases allowed knowledge regarding the way they teach mathematical and Portuguese written language contents to be brought to surface. The teachers exposed doubts, certainties, mistakes and contradictions that guided and characterized their professional practice. Processes of reflective inquiry related to their pedagogical practices were made evident. It can also be said that the teaching cases allowed the teachers to describe and analyze their own professional trajectories. Teachers pointed out that the peculiarities that characterized their first years of teaching showed that each of them experienced that period in a deeply personal manner, because of a series of elements that varied widely from teacher to teacher: the conceptions that she possesses regarding her profession; the relations that she establishes with peers, parents of pupils and pupils themselves; her first days of work; the way she deals with the subject matters that she must teach; theoretical quarrels that emerge as the children learn; the way she conceives the possibilities to continue learning despite the constraints of the profession. The use of teaching cases made it possible for teachers to become aware of the complexities that characterize their learning to teach processes, and to develop important strategies to promote and to investigate such processes.